Board diversity and financial sustainability in charities: a Malaysian perspective - Cheuk, Sharon; Nichol, Esmie Obrin; Tinggi, Michael; Daw, Tin Hla (Universiti Malaysia Sarawak (UNIMAS), 2017)
Charity failure has been a problem that has been plaguing developed countries and developing alike. In Malaysia, it has been reported that charities faced difficulties in raising donations due to the difficult economic climate. Past research has provided some evidence on the role of board diversity on the financial performance of for-profit organizations. This study examines the impact of board diversity in improving charity financial sustainability. A sample of 211 active charities (companies limited by guarantee) in 2016 was selected. Data on board diversity (age, gender, race and tenure) as well as financial sustainability were obtained and binary logistic regression via XLSTAT was performed. The findings suggested that director tenure diversity significantly predicts financial sustainability of charities. Age, race and ethnic diversity were found to be not significant. The implications of the study’s findings mean that charities in general should embark upon regular new director appointments, in order to maintain a fresh outlook and to bring in new infusion of skills at the strategic and operational levels.